2020
DOI: 10.1080/03004430.2020.1832997
|View full text |Cite|
|
Sign up to set email alerts
|

Presence of parent, gender and emotional valence influences preschoolers' PFC processing of video stimuli

Abstract: Due to an unprecedented increase in children's exposure to a wide range of video stimuli, there is a need to understand how they process them. From the tender age of 3, children show distinct activations in the prefrontal cortex (PFC) when presented with children's movies. However, there are multiple factors that can influence child neural response to such screen media, namely, presence of a specific parent, gender differences and emotional valence. Sixty-two preschool children (37 boys) between ages 3 and 4 i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…A dataset of parent–child hyperscanning fNIRS data [ 17 ] was used to evaluate the feasibility of the heart rate estimation on fNIRS data. This dataset has been used to study the synchrony between parents and children during shared video watching and play [ 18 , 19 , 20 , 21 ]. It was selected among others because: (a) it includes subjects from two age groups: adults and children; and (b) it collects data during two experimental conditions: while the subjects were watching some videos (thus, few MA are expected), and while the subjects were playing (more MA expected).…”
Section: Methodsmentioning
confidence: 99%
“…A dataset of parent–child hyperscanning fNIRS data [ 17 ] was used to evaluate the feasibility of the heart rate estimation on fNIRS data. This dataset has been used to study the synchrony between parents and children during shared video watching and play [ 18 , 19 , 20 , 21 ]. It was selected among others because: (a) it includes subjects from two age groups: adults and children; and (b) it collects data during two experimental conditions: while the subjects were watching some videos (thus, few MA are expected), and while the subjects were playing (more MA expected).…”
Section: Methodsmentioning
confidence: 99%
“…This study is a subset of a larger fNIRS project investigating parent-child dyads, which consists of two tasks. The co-viewing task involves dyads viewing animations together; studies have found that dyadic neural activities are associated with psychological variables including parenting stress, attachment, and gender differences [17,[26][27][28]. The second task is a play activity, where a behavioural paper on the correlation between dyadic emotional availability, past interactions, and parenting stress [29], as well as a technical study on optimising parameters and strategies during the computation of inter-brain synchrony [30] have been published.…”
Section: Methodsmentioning
confidence: 99%
“…Fathers of sons showed greater PFC activation than mothers of sons when co-viewing the conflict scene from The Incredibles, whereas mothers of daughters showed greater PFC activation than fathers of daughters when viewing the conflict scene. The findings from this chapter have been accepted for publication in Durnford, Balagtas, Azhari et. al (2020).…”
Section: Discussionmentioning
confidence: 91%
“…On the contrary, partners tend to synchronise to situations that do not elicit distress so as to remain socially attuned to each other's emotional states. In another study, Bizzego et al (2020) examined the degree of physiological synchrony across romantic partners, friends and strangers when each pair was presented with video vignettes which elicited different emotional conditions (i.e., fear, embarrassment, romance, pride, sadness, calmness/neutral). They demonstrated that romantic partners displayed significantly greater synchrony towards the neutral non-social stimulus which depicted a scene of waves rolling onto the beach.…”
Section: Discussionmentioning
confidence: 99%